Factor analysis for construct validity of a trunk impairment scale in Parkinson’s disease: a cross-sectional study - Sato, Kazunori; Yamazaki, Yuta; Kameyama, Yoshihiro; Watanabe, Koji; Kitahara, Eriko; Haruyama, Koshiro; Takahashi, Yoko; Fujino, Yuji; Yamaguchi, Tomofumi; Matsuda, Tadamitsu; Makabe, Hitoshi; Isayama, Reina; et al. (Frontiers in Neurology, 2024)
To investigate the construct validity of the Trunk Impairment Scale (TIS), which was developed to assess trunk impairment in patients with stroke, in patients with Parkinson's disease (PD).This retrospective, cross-sectional study enrolled consecutive PD inpatients. Correlation analysis was performed to clarify whether the TIS assessment was related to other balance functions, lower extremity muscle strength, or walking ability. Factor analysis was performed to see how the background factors of TIS differ from balance function, lower limb muscle strength, and walking ability.Examining the data of 471 patients with PD, there were relationships between TIS and the Mini-Balance Evaluation Systems Test (r=0.67), Barthel Index (r=0.57), general lower limb extension torque (r=0.51), two-minute walk test (r=0.54), Hoehn and Yahr stage (r=-0.61), and Movement Disorder Society Unified Parkinson's Disease Rating Scale part III total points (r=-0.59). Factor analysis showed that TIS items were divided into three factors (an abdominal muscles and righting reflex component; a perception and verticality component; and a rotational component), differing from other scales that included clinical assessment items.The TIS can be useful for assessing the underlying trunk impairment as a basis for activities of daily living, gait function, and balance ability in patients with PD.